Preparation and Characterization of Thermally Conductive High Impact Polystyrene/AlN Composite - Nghiem Thi Thuong; Nguyen Ba Lam; Pham Anh Son; Nguyen Ba Chien; Nguyen Pham Duy Linh; Chu Thi Hai Nam; Nguyen Anh Vu (International Journal of Polymer Science)
In the present work, AlN was modified with vinyltriethoxysilane (VTES), and its effect on the properties of a thermally conductive composite of high impact polystyrene (HIPS), and AlN was investigated. Three composites, HIPS/AlN5, HIPS/AlN9, and HIPS/moAlN9, were prepared by mixing HIPS and AlN in a toluene solution, followed by hot pressing. The HIPS/AlN composite was characterized by tensile test, impact strength, flexural strength, and hardness shore D. The sample HIPS/moAlN9 showed the improvement of these properties compared to that of the HIPS/AlN9 sample. The increment of those mechanical properties was due to the good interaction between the modified AlN and HIPS resin matrix, which was revealed by morphology observation by SEM. Incorporating modified AlN into the HIPS matrix was also found to enhance the thermal conductivity by about 20%, from 0.15 for HIPS to 0.18 (W/m·K) for HIPS/moAlN9. It was explained due to the good adherence of AlN to the HIPS, which provided more thermal conductive routes than HIPS/AlN. This approach provides a possible strategy to prepare thermally conductive HIPS composite, which may be suitable for electronic device that required heat dissipation.